2020
DOI: 10.1136/bjophthalmol-2019-315381
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival lymphangiectasia as a biomarker of severe systemic disease in Ser77Tyr hereditary transthyretin amyloidosis

Abstract: AimsTo investigate the relationship between the ophthalmic and systemic phenotypes in patients with hereditary transthyretin amyloidosis with the S77Y mutation (ATTRS77Y).MethodsIn this cross-sectional study, patients with genetically confirmed ATTRS77Y amyloidosis were enrolled. All patients underwent complete neurological examination, including staging with the Neuropathy Impairment Score (NIS), Polyneuropathy Disability (PND) score; complete cardiological evaluation, including echocardiography, cardiac MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…These results are in line with previous reports 3,5,8,11,12 with variations of different signs prevalent probably because of the different distribution of genetic variants in different geographic areas.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with previous reports 3,5,8,11,12 with variations of different signs prevalent probably because of the different distribution of genetic variants in different geographic areas.…”
Section: Discussionsupporting
confidence: 93%
“… 10 Two other studies with ICG confirmed these changes in ATTRv patients. 23 , 24 Marta et al evaluated the choroidal vascularization with OCT in ATTRv patients. 9 They found higher stromal area, a lower choroidal thickness, and lower choroidal vascularity index, compared with a control group of age-matched healthy patients.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Reportedly, ocular findings vary with TTR variants. 12 The main ocular symptoms of hATTR-V30M include irregular pupils, dry eyes, amyloid angiopathy, vitreous opacity, and glaucoma. 13–18…”
mentioning
confidence: 99%